Communication languages and educational challenges: the problem of young teachers formation - Citelli, Adilson (Comunicação & Educação, 2010)
This text systematizes data collected in the research that discusses the interface between communication and education. The main objective is to verify how young teachers from fundamental and medium school systems, in the age groupup to 30 years old, are living and working with new media cultures